Immigrant-native differences in welfare participation: the role of entry and exit rates - Jörgen Hansen; Magnus Lofstrom (Institute for the Study of Labor (IZA), 2006)
This paper analyzes differences in welfare transitions between natives and immigrants in Sweden using a large representative panel data set, LINDA, for the years 1991 to 2001. The data contains administrative information on welfare use, country of birth, and time of arrival in Sweden among other things, and provides an excellent opportunity to examine immigrant-native differences in welfare use. The empirical results suggest that the main reason for the large immigrant-native welfare gap observed in the data is differences in welfare entry rates. Thus, policies aimed to reduce these transitions may be particularly successful in reducing welfare use in general and the immigrant-native welfare gap in particular.
Keywords: I30; I38; J15; J18; J61; 330; welfare; immigration; labor market behavior; transition; state dependence